DARK TRIAD PERSONALITY IN EKA KURNIAWAN’S NOVEL LELAKI HARIMAU - Pardi, Pardi; Sonia, Trisya (Universitas Islam Sumatera Utara, 2025)
This study analyzes the Dark Triad personality in Margio’s character in Eka Kurniawan’s novel Lelaki Harimau. Employing a descriptive qualitative methodology with document analysis, this research systematically examines the intricate manifestations of Machiavellianism, Narcissism, and Psychopathy within the protagonist's psychological profile and investigates how this specific personality configuration fundamentally drives the narrative trajectory. The findings demonstrate that Margio exhibits a pronounced and comprehensive constellation of all three dark personality traits: strategic manipulation and social duplicity characteristic of Machiavellianism, grandiose self-concept and supernatural tiger spirit belief reflective of Narcissism, and impulsive aggression coupled with complete absence of remorse indicative of Psychopathy. These traits operate synergistically rather than in isolation - his Machiavellian cunning enables the violence, his Psychopathic affect permits its execution without emotional consequence, and his Narcissistic grandiosity provides psychological justification for his actions. The study concludes that Margio represents a compelling literary representation of the Dark Triad personality, developed through traumatic environmental circumstances and childhood adversity. This research contributes significantly to psychological literary criticism within Indonesian fiction by providing a nuanced framework for understanding complex character motivations and the psychological underpinnings of literary violence.